Qinghaosu in combinations. - White, N (1998)
Antimalarial combinations make therapeutic sense. As we have few antimalarial drugs and even fewer in development, and as the malaria parasite shows a remarkable ability to develop resistance, all possible measures should be taken to protect those drugs that we do have available. Although in experimental animals combinations have been shown unequivocally to delay the onset of resistance, this has not yet been proved formally in human malaria. Yet formal proof is extremely difficult to obtain. However, there is sufficient circumstantial evidence to suggest that resistance can be delayed. As there are no counter arguments and the stakes are high, it seems reasonable that an artemisinin derivative should be combined with all slow acting antimalarial drugs. Those drugs with a particularly vulnerable profile, in which a single or double point mutation confers high level resistance, should not be deployed alone and should always be combined with an artemisinin derivative.